2012
DOI: 10.1016/j.neuron.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Tuned Normalization Explains the Size of Attention Modulations

Abstract: SUMMARY The effect of attention on firing rates varies considerably within a single cortical area. The firing rate of some neurons is greatly modulated by attention while others are hardly affected. The reason for this variability across neurons is unknown. We found that the variability in attention modulation across neurons in area MT of macaques can be well explained by variability in the strength of tuned normalization across neurons. The presence of tuned normalization also explains a striking asymmetry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
159
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(177 citation statements)
references
References 63 publications
(110 reference statements)
17
159
1
Order By: Relevance
“…22,23]. Here, each neuron is normalized not only by its suppressive surround, but also by its own net-excitatory input.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23]. Here, each neuron is normalized not only by its suppressive surround, but also by its own net-excitatory input.…”
Section: Resultsmentioning
confidence: 99%
“…Such a mechanism was previously shown to be a vital component in a model capturing the response properties of direction-selective neurons in extrastriate cortex [22]. The tuned normalization in another recent report [23] is also conceptually similar: here, the authors showed that MT neuronal responses to a pair of stimuli within the receptive field (one moving in the preferred direction and the other in the anti-preferred direction) were well explained by direction-tuned divisive normalization. The majority of neurons in their data showed a greater normalizing influence of the preferred stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have investigated “sensory” conditions, i.e., when none of the stimuli were behaviorally relevant (Snowden et al, 1991; Recanzone et al, 1997; Britten and Heuer, 1999; Treue et al, 2000; Majaj et al, 2007), as well as “attentional” conditions, i.e., task designs where one of the stimuli were behaviorally relevant (Seidemann and Newsome, 1999; Treue and Trujillo, 1999; Patzwahl and Treue, 2009; Niebergall et al, 2011a,b; Ni et al, 2012). All of these studies implicitly or explicitly assume that neurons always respond to multiple stimuli in their receptive field with a single response state that represents an integration (averaging with or without scaling or gain control) of the individual stimulus responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, normalization is a computational process that explains the well-known observation that presenting two stimuli in a sensory cortical neuron’s response field results in neuronal activity that is approximately the average of the responses of the neuron to the presentation of each stimulus alone, rather than the sum. Normalization provides a description of how neurons integrate their multiple sources of excitatory and inhibitory inputs and is a key computation thought to underlie attention (Boynton 2009, Carandini & Heeger 2012, Lee & Maunsell 2009, Maunsell 2015, Ni et al 2012, Reynolds & Heeger 2009). In vivo, collicular neurons show properties of normalization similar to those seen in the visual cortex.…”
Section: Microcircuits Of the Superior Colliculusmentioning
confidence: 99%